Temporal and spatial patterns of dengue geographical distribution in Jeddah, Saudi Arabia - Hissah Al-Nefaie; Amirah Alsultan; Raghib Abusaris (Elsevier, 2022)
Introduction: Dengue fever disease is affected by many scoioeconomic and enviromental factors throughout endemic areas globally. These factors contribute to increase the incidence of endemic dengue endemic in Jeddah, Saudi Arabia. Objectives: This study aimed to investigate the distribution and spatial patterns of dengue fever cases in Jeddah, and to determine if there is an association between dengue fever and the following environmental factors: temperature, humidity, land cover, climate, rainfall, epicenter of reproduction, and socioeconomic factors. Methods: A descriptive and analytical cross-sectional study was conducted in Jeddah in 2020. The study included all reported suspected and confirmed dengue cases. The sample size was 1458 cases. Data were obtained from the Dengue Active Surveillance System and the confirmed cases were geo-distributed in areas by QGIS. All significant variables were included in the logistic regression table. Results: The majority (61.9 %) were suspected cases and 38.1 % confirmed cases. The majority of the cases were male. The highest spatial distribution was in the middle of Jeddah and the lowest in the south. The highest temporal distribution for confirmed cases was in June, and for suspected cases in December. Age, gender, occupation, and area were all significantly associated with the dengue reported cases. Most all the enviromental factors were not statistically significant. Conclusion: The study showed three clusters of dengue fever and infection concentrated in the middle and east of Jeddah. The lack of investigation in the environmental factors regarding the dengue distribution and its impact on the population area has to be taken seriously and dengue intervention programs should be implemented to reduce the endemic dengue in Jeddah.